Shared decision making: Concepts, evidence, and practice - Stiggelbout, A.M.; Pieterse, A.H.; De Haes, J.C.J.M. (Patient education and counseling, 2015)
•Shared decision making (SDM) became much debated in the last decades of the 20th century.•Four steps can be distinguished anad our paper provides suggestions how to perform these.•The steps have been found not be widely implemented in clinical practice.•For implementation various strategies are needed, targeting both professionals and patients. Shared decision-making (SDM) is advocated as the model for decision-making in preference-sensitive decisions. In this paper we sketch the history of the concept of SDM, evidence on the occurrence of the steps in daily practice, and provide a clinical audience with communication strategies to support the steps involved. Finally, we discuss ways to improve the implementation of SDM. The plea for SDM originated almost simultaneously in medical ethics and health services research. Four steps can be distinguished: (1) the professional informs the patient that a decision is to be made and that the patient's opinion is important; (2) the professional explains the options and their pros and cons; (3) the professional and the patient discuss the patient's preferences and the professional supports the patient in deliberation; (4) the professional and patient discuss the patient’s wish to make the decision, they make or defer the decision, and discuss follow-up. In practice these steps are seen to occur to a limited extent. Knowledge and awareness among both professionals and patients as well as tools and skills training are needed for SDM to become widely implemented. Professionals may use the steps and accompanying communication strategies to implement SDM.